GAMIFICATION TECHNIQUES FOR TEACHING MUSIC THEORY USING DIGITAL PLATFORMS - Jalilov Shokir Isomiddinovich (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2026)
This article explores gamification techniques in teaching music theory through digital platforms. It examines strategies that integrate game elements such as points, badges, levels, and challenges to enhance student engagement, motivation, and learning outcomes. The paper discusses digital tools and interactive platforms that support gamified music theory lessons, emphasizing their role in improving comprehension, auditory skills, and creative thinking. The effectiveness of gamification in fostering active, student-centered learning and reinforcing theoretical knowledge is also analyzed.